Load bearing capacity of LSF walls under fire exposure - Piloto, P.A.G. (2018)
Light steel frame and prefabricated panels are widely used in loadbearing walls, with direct application to steel framed buildings. These walls are made with steel cold formed sections (studs and tracks) using gypsum plasterboard, other material layers attached to the flanges and sometimes insulation material in the cavities.